ORIENTASI KEPRIBADIAN DAN PENGARUHNYA TERHADAP PRESTASI DALAM OLAHRAGA - Taufik Rahman, (Ordik, 2012)
Psychological aspect is one of the factor that determines an athlete achievement. The psychology aspect is personality. In addition to hard training, athletes must have a strong personality in order to achieve the highest achievement. The personality that is defined in this research is locus of control which consist of internality, powerful others, and chance. The problem of this research were (1) is there difference in personality orientation between high achiever athletes and low achiever athletes?, (2) is the orientation of personality is influenced by gender?, (3) is the orientation of personality is influenced by the type of sport?. This research aimed (1) to determine the personality orientation between high achiever athletes and low achiever athletes, (2) to determine whether the orientation of the athletes personality is influenced by gender, (3) to determine wheter the orientation of the athletes personality is influenced by the type of sport. This type of research is non experimental quantitative research (ex- post facto) with the survey approach. The independent variable in this research is personality, the dependent variable is the achievement ang the attributive variables were gender and type of sport. The sample of this research is as many as 204 by using purposive sampling technique, which consists of high achiever and low achiever athletes, male and female athletes, athletes in individual sports and group sports. Analysis of the data used is the one way anova. The result showed that there is influenced of personality on achievement in sport. High achiever athletes have internality with a value of 4,682 with significant value 0,032. Female athletes have chance with a value of 9,904 with significant value 0,002. Athletes in individual sports have internality with a value of 25,471 with significant value 0,000 and have chance with a value of 7,443 with significant value 0,007.